2017
DOI: 10.1111/head.13178
|View full text |Cite
|
Sign up to set email alerts
|

A Nursing Intervention Increases Quality of Life and Self‐Efficacy in Migraine: A 1‐Year Prospective Controlled Trial

Abstract: A nursing intervention can lower the impact of migraines on the patient's life. The improvement in the HIT-6 score in this study was correlated with improvements in self-efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 46 publications
(74 reference statements)
2
11
0
Order By: Relevance
“…In their study, Leroux et al attempted to investigate the effect of nursing intervention on the quality of life and self-efficacy of the patients with migraine. They showed that these interventions proved useful and positive (38). In a systematic review study, Castillo-Bueno et al emphasized that nursing interventions can reduce pain (23), which is consistent with the results of the current study.…”
Section: Discussionsupporting
confidence: 90%
“…In their study, Leroux et al attempted to investigate the effect of nursing intervention on the quality of life and self-efficacy of the patients with migraine. They showed that these interventions proved useful and positive (38). In a systematic review study, Castillo-Bueno et al emphasized that nursing interventions can reduce pain (23), which is consistent with the results of the current study.…”
Section: Discussionsupporting
confidence: 90%
“…Limited task delegation was reported in some countries because of legislative limitations. However, different levels of nurse engagement in patient management were observed within the same country, suggesting the opportunity for every network to re-evaluate the role of nurses in caring for patients with migraine 8.…”
mentioning
confidence: 99%
“…SPSS18.0 statistical software was used for data processing. Statistical data were compared using X 2 test, and P < 0.05 was considered statistically significant [ 17 ].…”
Section: Methodsmentioning
confidence: 99%